The community drug distributor passport: a case study of training and recognition in Chad - Sohaibou Diane; Adoum Mahamat Oumar; Barka Kali; Danny Harvey; Nurudeen Dauda; Geordie Woods; Oladele Akogun; Philip Downs (Frontiers in Public Health, 2026)
Introduction Community health workers (CHWs), particularly volunteer community drug distributors (CDDs), play essential roles in advancing universal health coverage (UHC) and neglected tropical disease (NTD) control, yet their responsibilities and formal recognition remain poorly defined across health systems. This creates policy-implementation disconnects, especially during mass drug administration (MDA) campaigns for schistosomiasis and soil-transmitted helminthiases, where CDDs deliver critical services amid declining motivation and weak community awareness. Methods From 15 September 2023 to 1 February 2024, Sightsavers, the organization for the prevention of blindness, and Chad’s Ministry of Health and public prevention co-developed and piloted the CDD passport—a training and reference tool to clarify roles, build capacity, and formally recognize CDDs. Implemented during national MDA campaigns, the passport provided accessible materials on responsibilities, treatment protocols, and safety, alongside certificates acknowledging contributions. Results Pre-passport assessments revealed CDDs’ limited understanding of their roles, poor community knowledge of MDA objectives, and motivational challenges. Qualitative evaluations post-pilot—with health workers, CDDs, and community members—demonstrated improved knowledge retention, enhanced perceptions of CDD legitimacy, and stronger campaign performance. Government involvement highlighted broader CHW policy gaps, including how community settlement patterns affect delivery logistics. Discussion This community case study demonstrates how the CDD passport bridges CHW policy gaps by standardizing training, boosting motivation through recognition, and prompting national discussions on integrating volunteers into health systems. This innovation strengthens MDA effectiveness, supports sustainable NTD control, and models scalable universal health coverage (UHC) approaches for community health platforms in resource-constrained settings. Longer-term evaluation is needed to assess impacts on treatment coverage, volunteer retention, health outcomes, and cost-effectiveness.